Correlations among morphology, composition, and photoelectrochemical water splitting properties of InGaN nanorods grown by molecular beam epitaxy. (27th September 2018) - Xu, Zhenzhu; Zhang, Shuguang; Gao, Fangliang; Wen, Lei; Yu, Yuefeng; Li, Guoqiang
Abstract: The mechanism underlying the effect of growth condition on the morphology evolution of InGaN nanorods (NRs) has been systematically investigated. The increased Ga flux enhances both the axial and the radial growth at the growth stage. However, the changed Ga flux influences not only the growth but also the nucleation of InGaN NRs. At the nucleation stage, the increased Ga flux shortens the delay time for NR formation, and prolongs the growth stage for a fixed total growth time. Those two aspects result in the increase of NR diameter and height with the supplied Ga flux. In addition, the continuous nucleation is ended much earlier due to the accelerated saturation of substrate area with the increased Ga flux, resulting in a decreased final NR density. In addition to the morphology evolution with the Ga flux, the composition characteristic of InGaN NRs has been also studied. The In distribution of InGaN NRs depends critically on the NR diameter along the NR growth direction, and the NRs show a morphology-dependent In incorporation. Interestingly, the InGaN NRs discussed here show a radial Stark effect induced by the pinned Fermi level. The radial Stark effect shifts the absorption edge of the InGaN NRs toward longer wavelengths, makes the InGaN NRs attractive for photoelectrochemical water splitting applications. The photoelectrochemical measurements present a significant increase in the photocurrent with the increased total surface area of the InGaN NRs, which is due to the enhanced light absorption effects and the enlarged interfacial area of the semiconductor/electrolyte.